Congenital malformations of the head and neck - Zur, Karen B.; Elden, Lisa M. (Springer New York, 2014)
Congenital Malformations of the Head and Neck offers a unique conceptual and visual approach to children with congenital malformations of the head and neck. Developed by renowned leaders in the field, this title is richly illustrated with a wealth of patient photos, radiology and endoscopic images of malformations. Starting with the genetics of common congenital syndromes, Congenital Malformations of the Head and Neck goes on to comprehensively cover malformations of the ear, nose, nasopharynx, oral cavity, oropharynx, cleft lip and palate, larynx, trachea, and neck.  Easy-to-read and an indispensable reference and teaching resource, this title will serve as an invaluable reference for clinicians, neurologists, pediatricians, otolaryngologists and head and neck surgeons. It should also be of great interest to fellows and residents.